Lost boys : the thirst [videorecording (DVD)] - Piana, Dario; Charnov, Evan; Rodionoff, Hans; Feldman, Corey; Newlander, Jamison, 1970-; Phoenix, Tanit, 1980- (Warner Bros. Entertainment : Distributed by Warner Home Video, 2010)
After being hired by a novelist to protect her brother, Edgar Frog realizes that he is over his head and seeks the help of his brother Alan to fight an alpha vampire plotting against the lost youth of San Cazador.